2020
DOI: 10.1186/s12958-020-00636-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endometrial thickness and embryo quality on live-birth rate of fresh IVF/ICSI cycles: a retrospective cohort study

Abstract: Background: Successful implantation and delivery require both the functional embryo and receptive endometrium in assisted reproductive technology (ART) cycles. However, little is known about embryo-endometrial interaction on live-birth. We aimed to investigate the independent effect and interaction of endometrial thickness (EMT) and embryo quality on live-birth in fresh embryo transfer (ET) cycles. Methods: We conducted a retrospective cohort study including 15,012 ART cycles between 2013 and 2016 in three cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 40 publications
(63 reference statements)
0
20
0
Order By: Relevance
“…Hence, sensitivity analysis was conducted to detect the stability of result by removing each study and reanalyzing the remaining studies, which did not change the direction of the effect. When one study (21) was excluded, the substantial heterogeneity was decreased (I 2 declined from 62 to 0%). Women with thick endometrium (EMT >14 mm), had no significant higher LBR than those with medium EMT (7-14 mm) in fresh cycles (OR 1.08, 95%CI: 0.68, 1.72, P = 0.74, low heterogeneity: I 2 = 29%) (Figure 2B).…”
Section: Live Birth Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, sensitivity analysis was conducted to detect the stability of result by removing each study and reanalyzing the remaining studies, which did not change the direction of the effect. When one study (21) was excluded, the substantial heterogeneity was decreased (I 2 declined from 62 to 0%). Women with thick endometrium (EMT >14 mm), had no significant higher LBR than those with medium EMT (7-14 mm) in fresh cycles (OR 1.08, 95%CI: 0.68, 1.72, P = 0.74, low heterogeneity: I 2 = 29%) (Figure 2B).…”
Section: Live Birth Ratementioning
confidence: 99%
“…Similarly, this study was only for systematic review as well (20). Therefore, 22 studies were included for final meta-analysis (5,7,11,13,16,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Literature Selectionmentioning
confidence: 99%
“…In this study, patients with a wider intercornual distance (greater endometrial volume) were more likely to have a favorable pregnancy outcome (P = 0.0000). Some studies have reported a significant correlation between endometrial thickness and pregnancy rate [27,28]. A thin endometrium, usually associated with reduced blood flow, may fail to respond to hormone stimulation, leading to implantation failure or early miscarriage [29].…”
Section: Discussionmentioning
confidence: 99%
“…The studies from Lv Hong and Chen Shiping both showed that embryo quality and quantity are the main predictors for successful implantation and live birth [14,15]. Therefore, embryo quality is also critical for the outcome of ART [16,17].…”
Section: Introductionmentioning
confidence: 99%